Making aid work for education in developing countries: An analysis of aid effectiveness for primary education coverage and quality - Kassandra Birchler; Katharina Michaelowa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper examines the effect of education aid on primary enrolment and education quality. Using the most recent data on aid disbursements and econometric specifications inspired by the general aid effectiveness literature, we find some evidence that donors' increase in funding has substantially contributed to the successful increase in enrolment over the last 15 years. The most robust effect is obtained by aid for education facilities and training. In addition, we find complementarities between aid for primary and secondary education. Our qualitative comparative analysis of education quality also highlights the relevance of a balanced mix of educational expenditures.
Additional information: Corrigendum: In this working paper, we state that the main explanatory variable EDUCAID includes aid disbursements for education per capita of the recipient country population (in constant 2010 US). De facto, the findings reported for the article's econometric analysis reflect absolute aid rather than aid per capita. Since our main specifications are in logs the coefficient estimates of these regressions hardly change, however. When using EDUCAID in per capita terms as initially intended, the enrolment rate is estimated to increase by 6 percentage points, rather than 5.6 percentage points (in Table 1, regression 4) when education aid is doubled. Moreover, the interaction term between facilities and teacher training (Table 2, Regression 14) turns positively significant. For the recalculation of all statistical tables and the corresponding graph, see the new online appendix below.
Keywords: O20; I21; 330; aid effectiveness; educational enrolment; education quality